2020
DOI: 10.1007/s00125-020-05095-7
|View full text |Cite
|
Sign up to set email alerts
|

The glucose-lowering effects of α-glucosidase inhibitor require a bile acid signal in mice

Abstract: Aims/hypothesis Bile-acid (BA) signalling is crucial in metabolism homeostasis and has recently been found to mediate the therapeutic effects of glucose-lowering treatments, including α-glucosidase inhibitor (AGI). However, the underlying mechanisms are yet to be clarified. We hypothesised that BA signalling may be required for the glucose-lowering effects and metabolic benefits of AGI. Methods Leptin receptor (Lepr)-knockout (KO) db/db mice and high-fat high-sucrose (HFHS)-fed Fxr (also known as Nr1h4)-KO mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 56 publications
(85 reference statements)
1
9
0
Order By: Relevance
“…We found that both the concentration and proportion of TβMCA were significantly elevated in caecum and ileum of Abx mice ( Figure 3(J–M) ). In addition, the ratio of TβMCA/TCA, an indicator of FXR inactivation [ 34 ], was also increased after antibiotic treatment in ileum, although it was not significant different in caecum ( Figure 3(N,O) ). Thus, deleting gut microbiota was responsible for the alterations in microbial BA metabolism, particularly in accumulating the levels of FXR antagonist TβMCA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that both the concentration and proportion of TβMCA were significantly elevated in caecum and ileum of Abx mice ( Figure 3(J–M) ). In addition, the ratio of TβMCA/TCA, an indicator of FXR inactivation [ 34 ], was also increased after antibiotic treatment in ileum, although it was not significant different in caecum ( Figure 3(N,O) ). Thus, deleting gut microbiota was responsible for the alterations in microbial BA metabolism, particularly in accumulating the levels of FXR antagonist TβMCA.…”
Section: Resultsmentioning
confidence: 99%
“…BAs in caecum content, ileum, liver and colon were extracted using methanol containing internal standards and measured according to previously reported methods [ 34 ]. BAs in different tissues and BA synthesis marker 7-hydroxy-4-cholesten-3-one (C4) in plasma were analysed using ultra-performance liquid chromatography (UPLC)-triple quadrupole time-off-light mass spectrometry (Waters Corp) [ 34 , 39 ]. All the BAs standards and 7-hydroxy-4-cholesten-3-one (C4) standard were purchased from Sigma-Aldrich.…”
Section: Methodsmentioning
confidence: 99%
“…60 However, the pleiotropic downstream effects of FXR vary across BAs, and the metabolic effects of different BA receptors in different organs are also vary. 9 The strength of the natural activators of FXR follows the order of CDCA> DCA> CA> LCA, 57 and the natural inhibitors of FXR are tauro-α-MCA (T-α-MCA), tauroβ-MCA (T-β-MCA) and UDCA. [61][62][63] Notably, glycodeoxycholic acid (GCDCA), TCA and TDCA are weak activators of FXR.…”
Section: Fxrmentioning
confidence: 99%
“…[4][5][6] In 1999, BAs were discovered to be endogenous ligands of farnesoid X receptor (FXR), 7,8 which is widely expressed in the intestine, liver, and kidney. 9,10 BAs are generated in the liver and stored in the gallbladder. Postprandially, BAs are secreted into the intestine and metabolized by the intestinal flora.…”
Section: Introductionmentioning
confidence: 99%
“…Gu et al reported that acarbose increased the abundance of Bifidobacterium and Lactobacillus , whereas the abundance of Bacteroides was decreased at the genus level; as a result, the abundance of microbial genes, which are associated with the bile acid metabolism, and plasma bile acid composition are altered. The association between the hypoglycemic effects of acarbose and bile acid signals was studied using genetically modified murine models [ 15 ]. Zhang et al also reported that acarbose contributed to the significant increase of Bifidobacterium and Lactobacillus at the genus level.…”
Section: Introductionmentioning
confidence: 99%